Nakirah and Ma’rifat Implementation in Al-Isra verse 1-30 and Nakirah and Ma’rifa Implementation Study Method for Madrasah Aliyah - Munawwarah, Muflikhatul; Kharitsah, Nabila; Solihah, Arini Lutfi; Aini, Zahrotul; Faida, Farah (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This research aims to study isim nakiroh and ma'rifat and their application in the Al-Qur'an Surah Al-Isra and determine appropriate learning methods for students at Madrasah Aliyah. This research uses a qualitative approach with a library research type. Data analysis in this study used the Milles and Huberman technique. Based on data analysis that has been carried out, isim nakiroh and ma'rifat in Surah Al-Isra' are mentioned in each verse. With the various findings of isim nakiroh and ma'rifat in Surah Al-Isra, analogy, and drill learning techniques are appropriate to use in this learning